Analisis Pengaruh Kebijakan Harga Tiket dan Kualitas Kenyamanan terhadap Kepuasan Pelanggan: Studi Kasus Kereta Api Argo Bromo Anggrek Jakarta-Surabaya - Dewanti, Retno (Bina Nusantara University, 2006)
Article explore the influence of the price regulation and pleasure quality versus customer satisfaction using linier regression and measure the performance level versus the customer needs using Cartesius Diagram in order to find the customer satisfactionindex. The result of this research showed that the quality of pleasure services was the highest follow by the price regulation.Keywords: